Longitudinal effects of childhood recreational gymnastics participation on bone development: The Young Recreational Gymnast Study - Erlandson, Marta C.; Chapelski, Matthew S.; Adam, Margo E. K.; Zaluski, Alexandra J.; Baxter-Jones, Adam D. G. (Frontiers in Endocrinology, 2025)
PurposePrevious research in the Young Recreational Gymnast Study (2006–2014) found bone benefits from involvement in recreational gymnastics during young childhood. The purpose of this study was to identify any longitudinal effects of recreational gymnastics exposure during childhood on adolescent bone health.MethodsFor the present analysis, longitudinal data were available from 118 participants (66 female participants; 33 gymnasts) of the original 178 who were recruited and assessed on between one and five measurement occasions (median 3) between 2008 and 2020. Peripheral quantitative computed tomography (pQCT) scans were completed at both the distal and shaft sites of their non-dominant radius and tibia. Multilevel random-effects models were constructed to assess differences in the development of bone content, density, and estimated bone strength between those exposed and not exposed to recreational gymnastics while controlling for biological age, sex, body weight, limb length, and physical activity.ResultsIndividuals who were exposed to recreational gymnastics during childhood were found to have greater total area, total content, bone strength index, trabecular area, trabecular content, and trabecular density at the distal radius compared to physically active controls. There were no differences at the radial shaft, distal tibia, or tibial shaft.ConclusionInvolvement in childhood recreational gymnastics may provide long-term benefits at the distal radius as individuals enter young adulthood.